Particulate matter in the air of cities in Belarus - Liudchik, Alexander; Akimov, Aleksandr; Melnik, Alena; Paulenka, Pavel (Journal of the Belarusian State University. Ecology, 2024)
Some features of air pollution are analyzed based on data from automatic observation sites of Republican center for hydrometeorology, control of radioactive contamination and environmental monitoring on the content of particles in the air of regional cities of Belarus and the Berezinsky Biosphere Reserve for the period 2012–2022. Average daily particle concentrations depend not only on the intensity of local pollution sources, but also on transportation from nearby and distant regions. Meteorological conditions therefore play a decisive role in the level of fine particle air pollution: they can contribute to the dispersion of particles emitted by local sources and the delivery from distant regions particles emitted into the air. The latter situations are relatively rare, but often connected with high levels of particulate air pollution. In Belarus, maximum monthly average particle concentrations are recorded mainly in the spring months. The cause of the spring maximum has not been identified. The highest levels of air pollution by particles are observed in Minsk and Gomel, which are also the leaders in gas pollution in Belarus. The lowest ones are in Brest, Grodno, Vitebsk and Mogilev. However, Brest ranks third after Gomel and Minsk in terms of gaseous air pollution. This confirms the findings of other publications that particle concentration cannot be a reliable estimate of overall air pollution. Noticeable changes (decrease) in particle concentration over the years were detected in Minsk at only one observation site. At other sites there have been no significant changes over the years. The same can be said about other regional cities with the exception of Brest, where in recent years an increase in particle concentrations in the ground air has been recorded.
Keywords: particulate matter; meteorological conditions; anthropogenic air pollution